A Distributed Trust and Reputation Framework for Mobile Ad Hoc Networks - Sen, Jaydip (Recent Trends in Network Security and Applications, 2010)
In a multi-hop mobile ad hoc network (MANET), mobile nodes cooperate to form a network without using any infrastructure such as access points or base stations. The mobility of the nodes and the fundamentally limited capacity of the wireless medium, together with wireless transmission effects such as attenuation, multi-path propagation, and interference combine to create significant challenges for security in MANETs. Traditional cryptographic mechanisms such as authentication and encryption are not capable of handling some kinds of attacks such as packet dropping by malicious nodes in MANETs. This paper presents a mechanism for detecting malicious packet dropping attacks in MANETs. The mechanism depends on a trust module on each node, which is based on the reputation value computed for that node by its neighbors. The reputation value of a node is computed based on its packet forwarding behavior in the network. The reputation information is gathered, stored and exchanged between the nodes, and computed under different scenario. The proposed protocol has been simulated in a network simulator. The simulation results show the efficiency of its performance.